Blending enzyme immobilization enabled high performance glucose sensor based on an n-channel organic electrochemical transistor - Cheng Shi; Xingyu Jiang; Qi Wang; Chuan Xiang; Xinyu Dong; Lifeng Chi; Lizhen Huang (Materials Research Express)
Organic electrochemical transistors (OECTs) have emerged as an advantageous choice for constructing biosensors due to their remarkable water compatibility, low operating voltage, and inherent amplification capability. However, the current research on bio-sensing based on OECTs predominantly employs p–type material PEDOT:PSS as the channel material. Nevertheless, the utilization of a single material and its depleting characteristics impose significant limitations on device miniaturization and integration applications. We present a high-sensitivity glucose sensor based on n-channel accumulation-type OECT through immobilization the glucose oxidase on Pt gate electrode with an blending approach. The glucose oxidase directly mixed with bovine serum albumin, chitosan and immolizied on the gate electode, demonstrating a stable and sensitive response to the glucose. The modified n-channel organic electrochemical transistor demonstrates a highly sensitive response to glucose across a concentration range from μ M to mM, with a quantified stable sensitivity over 2.69 mmol ^–1 by normalizing the current change with respect to concentration. The device also exhibits selectivity towards glucose (compared with high concentrations of lactic acid, different concentration gradients of ascorbic acid, and uric acid), rendering it suitable for noninvasive glucose detection in body fluid like sweat, saliva etc This flexible and ensitive electrochemical transistor sensor holds immense potential for the development of potable healthcare biosensing.